The Basis of Art Appreciation - Desa, Noor Enfendi; Syed Abu Bakar, Syed Alwi; Muhamad, Noor A'yunni (Idealogy Journal; Vol 5 No 2 (2020): Idealogy Journal (September 2020), 2020)
This study revolves around identification of ways to observe or appreciate art since an artwork possesses its own aesthetic values which are related to a philosophy or an artist’s cognitive style in conveying the meaning behind an artistic piece. According to Kamus Dewan Edisi Ke-4 (2007), aesthetic is one of the branches of philosophy that deals with the nature of beauty and taste, as well as the philosophy of art. In this research, the two main parts involved are the definition of terms and an analysis on artwork. Three components in definition of terms are describing art and style, art and idea, as well as art and context.